The Effect of Foreign Loans, Exchange Rate of Rupiah/ USD, Inflation, Fed Rate, and Exports to Indonesia's Economic Growth - Slamet, Edy Juwono; Mubin, Muryani, M. Khoerul; Utami, Pelangi Dewi (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is one of the countries experiencing economic growth problems. The purpose of this study is to examine and analyze the effect of foreign loans, the exchange rate of rupiah/ USD, inflation, the Fed Rate, and exports to Indonesia's economic growth. The method of research in this study is ECM with period 2004 quarter I-2016 quarter IV. The conclusion is that in the long term, the variable of rupiah/USD exchange rate(X2) has a significant negative effect on economic growth, The Fed Rate(X4) has a significant positive effect on economic growth, and exports(X5) have a significant positive effect on economic growth, while in the short term variable exports(X5) have a significant positive effect on economic growth.